Academic and Gender Differences Among U.S. Otolaryngology Board Members. (30th July 2020) - Hill, Robert G.; Boeckermann, Lauren M.; Huwyler, Camille; Jiang, Nancy
Abstract : Objectives: To determine the representation of women in leadership positions within otolaryngology societies and to compare their academic rank and research productivity to men. Methods: The leadership positions of all U.S. otolaryngology societies were compiled. The Medicare Physician Compare database was used to obtain gender and medical school graduation year for all otolaryngologists. An online search was used to determine board member's academic faculty rank. The Scopus database was used to determine an individual's number of publications, citations, and h‐index. All websites were accessed from July 2019 to October 2019. Results: Of the 200 leadership positions, there were 160 unique individuals available for analysis. Of those, 23% were female. In comparison, 18% of all otolaryngologists in the United States are female. The average medical school graduation year was significantly more recent for female leaders (1997 vs. 1990, P  < .001) than males, which is similar to all otolaryngologists (2001 vs. 1993, P  < .001). Stratifying by gender alone, women averaged significantly fewer publications, citations, and h‐indices compared to men ( P  < .05), and were also less likely to be professors ( P  < .01). When considering both gender and graduation year, significant differences among academic productivity were only noted for those graduating between 1990 to 1999. Among all board members who graduated after 2000, women comprised a majority of those in leadership positions (52%). Conclusion: Leadership positions in otolaryngology societies reflect the changing demographic of otolaryngologists in the United States. There is proportionate representation, and the more recently graduated female physicians show the same research productivity as their male counterparts. Level of Evidence: 4 Laryngoscope, 131:731–736, 2021